Aplicação do método da busca harmônica na otimização de pórticos planos de concreto armado - Boito, Deise (2016)
In civil construction, the constructive methods and structural designs have been constantly evolving in search of rationalizing the consumption of materials and resource use efficiency, however, it is still one of the sectors that most uses natur al resources in its activities, causing impacts to the environment. In the search for a better solution to these factors, it is essential the application of techniques and solutions for conducting more effective and less costly projects. The structures optimization techniques in this context are inserted to replace the conventional design method based on intuition and experience of the engineer, through trial and error process, thus enabling, a more economical dimensioning of structures aiming towards sustainability. This paper introduces the development and implementation of a formulation for minimizing the costs of reinforced concrete plane frames through the optimization of the cross section of beams and columns and the application of the heurist ic method of optimization Harmony Search. In order to prove the efficiency of mathematical formulation and employed optimization method, a series of numerical analyses were performed. The heuristic method Harmony Search as well as the developed formulat ion presented good results, proving the efficiency of both in obtaining the minimum cost and presenting different parameters for optimal sizing of plane frames.